EVALUASI DAMPAK PROGRAM KAWASAN RUMAH PANGAN LESTARI KABUPATEN PACITAN - Hendratmo Noviyanto (JI@P, 2021)
Food security at the household level has a very basic development perspective. This is due to access to food availability and balanced nutrition is a human right. The formation of quality human resources is greatly influenced by the success of meeting the adequacy of food needs and food security, so food is one of the strategic elements in economic development and national security. The study entitled "Evaluation of the Impact of the Sustainable Food Houses Area Program in Pacitan District" has the formulation of the problem of How the Impact of the Sustainable Food Houses Area Program (KRPL) on meeting food needs, increasing income and productive efforts of the community. The purpose of this study is to describe / analyze the impact of the Sustainable Food Home Areas Program (KRPL) on meeting food needs, increasing income and community productive efforts. This research uses a qualitative research method with a descriptive approach. The data sources used are primary and secondary data, interviews and observation. Data analyzed with descriptive method. The foundation used is the Impact Evaluation theory (Thomas R. Dye) From the data analysis conducted, it was concluded that the Sustainable Food Home Area Program in Pacitan District had an impact on the availability, access, food consumption, efficiency of household expenditure and community income through the productive efforts of the community of Pacitan Regency. This program needs to be continued with the development of technologies and innovations that support the program's sustainability.